#1

It's Algebra 1, really. Whatever.

Solve using elimination:

4x=3y-18

4y=3x+17

Step-by-step would be a lot of help. Thanks!

Solve using elimination:

4x=3y-18

4y=3x+17

Step-by-step would be a lot of help. Thanks!

#2

combine like terms then isolate the variable.

edit: should it be

4x=3y-18

4y=3x+17

4x= 3y-18

x=-1

4y=3(-1)+17

4y=14

edit2ops forgot to multiply through.

edit: should it be

4x=3y-18

4y=3x+17

4x= 3y-18

__+ -3x=-4y+17__x=-1

4y=3(-1)+17

4y=14

edit2ops forgot to multiply through.

*Last edited by dubstar92 at Dec 9, 2008,*

#3

Have you even given it a go? Show us what you've tried to do.

#4

6+1.25x=y

-17+1.25x=y

thats either right or i made up a new math

-17+1.25x=y

thats either right or i made up a new math

#5

Have you even given it a go? Show us what you've tried to do.

I've kinda forgotten how to do it.

#6

i did this last year and hated it!! and i think u have to get the y by it self by dividing 3 or something. idk lol

#8

don't you need calculus for that? i did calculus last year, It all seems to have slipped my mind though

#9

4x=3y-18

4y=3x+17

are they 2 separate questions or do they go together

4y=3x+17

are they 2 separate questions or do they go together

#10

is it similtaneous(sp?)

#11

post reserved, help coming in a minute

4x=3y-18

4y=3x+17

first write the equations in standard form

4x-3y= -18

-3x+4y= 17

multiply the top equation by 3 and the bottom by 4 (to let the x's cancel out)

12x - 9y = -54

-12x + 16y = 68

combine the two equations, the x's will cancel out, leaving only y

7y = 14

solve for y

y = 2

now plug this number in for y in one of the first two equations (doesn't matter which)

4(2) = 3x + 17

solve for x

-9 = 3x

x = -3

solution: x = -3 y = 2

or: (-3,2) (the point of intersection)

4x=3y-18

4y=3x+17

first write the equations in standard form

4x-3y= -18

-3x+4y= 17

multiply the top equation by 3 and the bottom by 4 (to let the x's cancel out)

12x - 9y = -54

-12x + 16y = 68

combine the two equations, the x's will cancel out, leaving only y

7y = 14

solve for y

y = 2

now plug this number in for y in one of the first two equations (doesn't matter which)

4(2) = 3x + 17

solve for x

-9 = 3x

x = -3

solution: x = -3 y = 2

or: (-3,2) (the point of intersection)

*Last edited by samick007 at Dec 9, 2008,*

#12

It's Algebra 1, really. Whatever.

Solve using elimination:

4x=3y-18

4y=3x+17

Step-by-step would be a lot of help. Thanks!

You need to multiply each of the equations by a certain number (can be different for each equation) so that either the X or Y values cancel out.

For example:

4x=3y-18

-3y=-4x-18 (got the X on the same side as on the second equation)

4y=3x+17

If you multiply the 1st equation by 3 and the second one by 4 then the X values will cancel out. Then solve for Y and plug it in into either of the equations to get X.

#13

Sooo easy!!

4x=3y-18

4y=3x+17

First off, put the variables on the same side, I'll do bottom since it is easier, so it should be like this:

4x=3y-18

-3x=-4y+17

Then you multiply to get the same number, so you multiply the top by the opposite of the bottom, and the bottom by (not opposite that time) the top.. so multiply the top line by 3 and the bottom by 4. You will get

12x=9y-54

-12x=-16y+68

Then you simply add downward, so you should get:

-7y+14

Then you add the 7y to the other side since you need to get it something to equal:

7y=14

Then you divide 7 into 14, so you should get:

y=2

I skipped some crap cause I didn't feel like going uber into it (I'm in Algebra 3/4 so I have to do my own homework in a bit anyways)

But yeah, then when you get y=2 you substitute it back into the original equation to find out what x equals:

4x=6-18

so you then simplify...

4x=-12

then you divide like earlier:

x=3

So: y=2, and x=3

You are welcome, sorry I didn't explain further but the rest of it is basic algebra that you should have learned at the beginning of the year

4x=3y-18

4y=3x+17

First off, put the variables on the same side, I'll do bottom since it is easier, so it should be like this:

4x=3y-18

-3x=-4y+17

Then you multiply to get the same number, so you multiply the top by the opposite of the bottom, and the bottom by (not opposite that time) the top.. so multiply the top line by 3 and the bottom by 4. You will get

12x=9y-54

-12x=-16y+68

Then you simply add downward, so you should get:

-7y+14

Then you add the 7y to the other side since you need to get it something to equal:

7y=14

Then you divide 7 into 14, so you should get:

y=2

I skipped some crap cause I didn't feel like going uber into it (I'm in Algebra 3/4 so I have to do my own homework in a bit anyways)

But yeah, then when you get y=2 you substitute it back into the original equation to find out what x equals:

4x=6-18

so you then simplify...

4x=-12

then you divide like earlier:

x=3

So: y=2, and x=3

You are welcome, sorry I didn't explain further but the rest of it is basic algebra that you should have learned at the beginning of the year

#14

I'm in multivariate calculus, which is stupid and doesn't even have numbers, but I believe crust_punk is right, after you multiply rearrange them to both equal the same x and substitute one into the other.

#15

Take one equation : solve it for one of the variables.

You'll have something like this : x = bla or y = bla

Now that that bla, and place it in the other equation where the appropriate variable is.

Solve for teh only variable remaining.

EDIT: nvm that's substitution i think.. what level is this (high-school, university?)

You'll have something like this : x = bla or y = bla

Now that that bla, and place it in the other equation where the appropriate variable is.

Solve for teh only variable remaining.

EDIT: nvm that's substitution i think.. what level is this (high-school, university?)

#16

Take one equation : solve it for one of the variables.

You'll have something like this : x = bla or y = bla

Now that that bla, and place it in the other equation where the appropriate variable is.

Solve for teh only variable remaining.

He needs to use both equations to get rid of either variable.

#17

Kay. Thanks guys!

#18

Take one equation : solve it for one of the variables.

You'll have something like this : x = bla or y = bla

Now that that bla, and place it in the other equation where the appropriate variable is.

Solve for teh only variable remaining.

EDIT: nvm that's substitution i think.. what level is this (high-school, university?)

yea that's substitution. dang I hope this is at least high school, if not earlier. I learned this stuff in 8th grade

#19

He needs to use both equations to get rid of either variable.

he means to use substitution. Isolate y then plug it into the other equation.

#20

#21

I searchbar'd it, but I couldn't find it. I figured I should just start up my own thread. Thanks for the link, though.